Politik Hukum Pemungutan Suara Ulang (PSU) Pilkada 2025: Legal Politics of Recount Elections in the 2025 Local Elections. - Ridhanie, Azhar; Rahmiati, Rahmiati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
A Recount Election (PSU) is a legal mechanism designed to restore the legitimacy of the results of local elections when serious violations have occurred. This article explores the political law governing the implementation of the 2025 Local Elections Recount, highlighting its normative aspects, judicial analysis, practical implementation, and constitutional implications. Using a juridical-normative approach and empirical data analysis, this paper explains how the political law of a Recount Election is codified, executed, and experienced at the local level. The study's findings indicate that while a Recount Election is designed as a democratic instrument, its implementation is fraught with technical and political challenges, as well as issues of public participation. The authors recommend improvements to regulations, strengthening of institutions, and enhanced political education as a prescription for fortifying local democracy.